Can Exercise Counteract Cancer Cachexia? A Systematic Literature Review and Meta-Analysis. (September 2020) - Niels, Timo; Tomanek, Annika; Freitag, Nils; Schumann, Moritz
Background: Cancer-cachexia is associated with chronic inflammation, impaired muscle metabolism and body mass loss, all of which are classical targets of physical exercise. Objectives: This systematic review and meta-analysis aimed to determine the effects of exercise on body and muscle mass in cachectic cancer hosts. Data Sources: PubMed/Medline, EMBASE, CINHAL, ISI Web of Science, and Cochrane Library were searched until July 2019. Study Selection: Trials had to be randomized controlled trials or controlled trials including cancer patients or animal models with cachexia-inducing tumors. Only sole exercise interventions over at least 7 days performed in a controlled environment were included. Data Extraction: Risk of bias was assessed and a random-effects model was used to pool effect sizes by standardized mean differences (SMD). Results: All eligible 20 studies were performed in rodents. Studies prescribed aerobic (n = 15), strength (n = 3) or combined training (n = 2). No statistical differences were observed for body mass and muscle weight of the gastrocnemius, soleus, and tibialis muscles between the exercise and control conditions (SMD = ‒0.05, 95%CI-0.64-0.55, P = 0.87). Exercise duration prior to tumor inoculation was a statistical moderator for changes in body mass under tumor presence ( P = 0.04). Limitations: No human trials were identified. A large study heterogeneity was present, probably due to different exercise modalities and outcome reporting. Conclusion: Exercise does not seem to affect cancer-cachexia in rodents. However, the linear regression revealed that exercise duration prior to tumor inoculation led to reduced cachexia-severity, possibly strengthening the rationale for the use of exercise in cancer patients at cachexia risk.